2012
DOI: 10.1371/journal.pone.0045415
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Patterns at Exhaustion in Rats That Differ in Inherent Exercise Capacity

Abstract: In order to further understand the genetic basis for variation in inherent (untrained) exercise capacity, we examined the brains of 32 male rats selectively bred for high or low running capacity (HCR and LCR, respectively). The aim was to characterize the activation patterns of brain regions potentially involved in differences in inherent running capacity between HCR and LCR. Using quantitative in situ hybridization techniques, we measured messenger ribonuclease (mRNA) levels of c-Fos, a marker of neuronal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…This response is consistent with recent findings that better exercise performance until exhaustion in rats with high running capacity was associated with an increase in c‐Fos mRNA levels in several brain areas, including the PVN. This result suggests that there is a potential difference in brain activation patterns that may contribute to the variation in inherent running capacity between individuals . Consistent with this background, this study found that neuronal activity in the PVN, the MPO and the MnPO directly correlated with the workload performed by the animals during incremental exercise until fatigue, indicating that the increased activation of these sites contributed to the improved physical performance seen in TR rats.…”
Section: Discussionsupporting
confidence: 79%
“…This response is consistent with recent findings that better exercise performance until exhaustion in rats with high running capacity was associated with an increase in c‐Fos mRNA levels in several brain areas, including the PVN. This result suggests that there is a potential difference in brain activation patterns that may contribute to the variation in inherent running capacity between individuals . Consistent with this background, this study found that neuronal activity in the PVN, the MPO and the MnPO directly correlated with the workload performed by the animals during incremental exercise until fatigue, indicating that the increased activation of these sites contributed to the improved physical performance seen in TR rats.…”
Section: Discussionsupporting
confidence: 79%
“…Based on the possibility that inherent (untrained) running capacity reflects inherent exercise-related traits, lines of rodents with higher or lower EC were established by selective breeding [ 6 , 17 ]. An exercise-testing protocol, rather than genetic selection, was created to select rodents with intrinsically higher and lower EC [ 18 , 19 , 20 ].…”
Section: Brain Areas and Functions Related To A Predisposition To mentioning
confidence: 99%
“…In addition to peripheral factors such as musculoskeletal and cardiopulmonary functions, the central nervous system (CNS) plays a pivotal role in athletic performance, as the brain controls the initiation and processing of physical activity [ 6 ], motor skill acquisition [ 7 ], regulation of physical activity [ 8 ], and psychological traits, including motivation to exercise, anxiety, and stress resilience [ 4 , 8 ]. In light of the relationship between the brain and physical activities, extensive studies on the effects of exercise on brain functions have reported that exercise is beneficial to cognitive function, potentially through multifactorial pathways that include improvement of cardiovascular conditions [ 9 ], adult neurogenesis [ 10 , 11 ], and modifications of neurotransmission by muscle-derived bioactive molecules [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exhaustion was defined as the third time when a rat could no longer keep pace with the speed of the treadmill belt and remained on an electric shock grid for 2 s rather than running. 15 No rat ceased to exercise because of foot or any other type of injury. The flow chart for experimental protocols is shown in Figure 1.…”
Section: Experimental Protocolsmentioning
confidence: 99%